Organic Waste Management for Making Eco Enzymes as an Effort to Recycle Household Organic Waste in the Baturetno Area - Meisari, Winda Azmi; Muhlizardy, Muhlizardy; Aulia, Salma Nur (Sarana Ilmu Indonesia (salnesia), 2025)
Eco enzymes produced from the fermentation of organic waste offer a potential solution for household organic waste recycling. This study aims to investigate household organic waste management practices for eco enzyme production as a recycling effort in Baturetno. The specific objectives of this study are to educate the public about the benefits and process of eco enzyme production, and to measure the program's effectiveness in reducing the volume of organic waste disposed of. This study used a descriptive qualitative approach and was conducted on Sunday, January 21, 2024, at a resident's home in RT 10, Bumen Wetan, Baturetno, Banguntapan, Bantul. This activity involved 15 participants who took part in outreach and training on organic waste management and eco enzyme production. Data were collected through direct observation and interviews with participants to gain an in-depth understanding of their practices and perceptions. The results of the activity showed that through outreach and training, participants gained a better understanding of the importance of organic waste management and the eco enzyme production process. Participants were able to practice making eco enzymes correctly using the tools and materials provided. The production of eco enzymes not only helps reduce the volume of organic waste but also results in a natural cleaning product suitable for everyday use. The active participation of the community in this program demonstrates the great potential for implementing similar practices in other communities